Articulating the Ḥijāba : cultural patronage and political legitimacy in al-Andalus, the Amirid regency c. 970-1010 AD - Rosser-Owen, Mariam (Handbook of Oriental studies. section 1 the Near and Middle East,, 2021)
"In Articulating the Ḥijāba, Mariam Rosser-Owen analyses for the first time the artistic and cultural patronage of the 'Amirid regents of the last Cordoban Umayyad caliph, Hisham II, a period rarely covered in the historiography of al-Andalus. Al-Mansur, the founder of this dynasty, is usually considered a usurper of caliphal authority, who pursued military victory at the expense of the transcendental achievements of the first two caliphs. But he also commissioned a vast extension to the Great Mosque of Cordoba, founded a palatine city, conducted skilled diplomatic relations, patronised a circle of court poets, and owned some of the most spectacular objects to survive from al-Andalus, in ivory and marble. This study presents the evidence for a reconsideration of this period"--